A methods engineering study on Stelleca Enterprises, Inc. - De Castro, Diana May (College of Engineering, 2003)
This paper is all about a study conducted on Stelleca Enterprises Inc., a manufacturing company producing mainly scrub suits. This study was composed of all the details in producing scrub suit, from acquisition of raw materials down to releasing the final products to customers. Aside from all the processes involved, worker's conditions, management's policies and all that are important in the company's present condition was also included. To be able to do this, methods engineering techniques like time study was applied. Also, problem solving tools were used in analyzing company's methods and procedures. Value Engineering was also essential in producing the best recommendation that will further improve the existing method of the company so as to increase the productivity of the laborers, to minimize cost of production, to use time effectively and efficiently, to maximize use of space, and to utilize resources efficiently. The group conducted series of company visits to be able to document their present way of doing the business. From these company visits, several problems were observed. Among these problems, six were considered root causes. These are having no manual, inefficient layout of equipment and materials, inefficient racking system, no records of consumption of raw materials, no definite policy on scrap disposal, and unclear job description. The company does not have a written standard operating procedure. Since no documentation can be found regarding different kinds of policies, records and systems, a lot of problems arise. To solve this problem, the company should produce a manual that would contain all the policies, standards and procedures needed not only in the production side but to the whole company as well. Some of the things needed to be put on the manual are worker's schedule, compensation, benefits, policy on acquiring raw material, recording system and worker's job description. For the problem inefficient layout of equipment and material, alternative layout one is the best choice. It would lessen the distances covered by each operation with a difference of 82.35 ft from the present layout. The time spent doing these operations would also be reduced by 0.223 minutes. Racking system is also very important especially with this kind of business. It will not only eliminate foreign elements like matching of fabric to thread but will also eliminate time and confusion from workers. A devised Number Coding System was suggested. This is a racking system where all the cabinets will be coded according to location. The same code will be used on the threads matching the color of the fabric. When the cutter gets the fabric he should note its code for the sewers so that the sewers can easily locate the matching thread to the fabric. It is very important to be able to match the thread and the fabric before putting it in the rack. Another problem of the company was the fact that they do not keep records of the consumption of raw materials. With this problem, they would not be able to know when they should replenish raw materials. Thus, it is possible that during production, a certain raw material will be unavailable. To prevent this case, it was suggested that the company should record consumption of raw materials daily. It is better to make recordings daily, compared to every two weeks and every month since it is easier to keep track of the consumed materials within short duration. Another problem facing all garments manufacturing was the disposal of scrap surplus. These could make the working area look messy and could interrupt workers. The best way to solve this was to sell these scraps to rug manufacturer every two weeks or as long as a lot of it has accumulated. The scraps should be collected from working area during a specific time of the day. This would not only solve the problem of messy working area but would also provide profit to the company. The estimated profit would be Php4900 per week. The last of the six root causes was the unclear job description. The management should produce a written document about what jobs should be assigned to different kinds of workers. They should also produce a board that would contain job descriptions with in the working area so that the workers can easily see all their responsibilities. Aside from the recommendations that would solve the problems, the group also suggested that the management should review the minimum quota set for production of scrub suit for each worker. Presently, the company set a quota of five units of scrub suit per worker each day. According to the time study conducted, an average worker can make six suits for an eight hour working day. The whole study was done to help the company. Implementations of these recommendations are still under the management's approval.